STUDI KEWENANGAN PEMERINTAH DAERAH : PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) SATUAN POLISI PAMONG PRAJA DI KABUPATEN PELALAWAN TAHUN 2014-2016 - Putra, Ari Kurniawan; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The local government of Pelalawan Regency is trying to make the Local Regulation work well, therefore it encourages the government to guard the local regulation by granting authority to other institutions outside Polri to be involved in the investigation process. The Civil Institution which is authorized to conduct an investigation is Civil Servant Investigator (PPNS) by authorizing the Regional Regulation of Pelalawan Regency No. 04 year 2014. Civil Servant Investigator (PPNS) is a certain Civil Service Officer who based on the legislation is appointed as the investigator and has the authority to conduct criminal investigation within the legal environment which becomes the legal basis of each. The authority given to Civil Servant Investigators (PPNS) is expected to assist the Pamong Praja Police Unit in Pelalawan District in enforcing the Local Regulation, one of them in the case of investigating the violation of Regional Regulation on Community Disease in Pelalawan Regency.This study aims to describe the authority of the Civil Servant Investigator (PPNS) of the Civil Service Police Unit and the obstacles of Civil Servant Investigator (PPNS) of the Civil Service Police Unit in Pelalawan Regency in the implementation of the investigation of violation of Regional Regulation No. 06 Year 2011 on Disease Society from 2014-2016. This research method using qualitative approach and using type of descriptive research method. Data collection techniques in this study using in-depth interview techniques and relevant fact documentation.Based on the results of interviews, data and information have been obtained it can be concluded that the Civil Service Investigator (PPNS) Civil Service Police Unit in Pelalawan District in carrying out its authority has been felt quite well, because it is in accordance with the authority that has been delegated. But in the implementation of the investigation of violations of Regional Regulation No. 06 Year 2011 on Community Disease there are also obstacles in carrying out its authority both internal factors namely, factors from within Civil Servant Investigator (PPNS) and external factors, factors that come from outside Civil Servant Investigator (PPNS) such as socio-cultural and economic.Keywords: Authority, Civil Service Investigator, Community Disease